Identitas Nasional dan Konstruksi Pasif dalam Bahasa Indonesia - Teguh, I Wayan (Humanis; Vol 27 No 2 (2023), 2023)
Bahasa Indonesia  have many functions. One of the functions is as the symbol of the national identity. This function is closely connected with the statement that “language is the mirrors of the nation”. This means that that the way of thinking of the nation can be learned through is language. This further means that language affects the way of thinking of the community as well as the way they perceive their environment. In connection to this, in this article is discussed one of the mirrors of the national identity, which is the bahasa Indonesia, particularly  the passive construction in this language. This considered of significance because in the passive construction the agent or the actor rule is not given.